Youth technical sessions proceedings : proceedings of the VI Youth Forum of the World Petroleum Council - Future Leaders Forum Saint Petersburg, Russian Federation, 23-28 June, 2019 - Litvinenko, Vladimir (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
Over a decade ago the World Petroleum Council launched an initiative to hold an international professional youth forum. The first forum took place in October 2004 in China, and had as its motto: "Young people and innovations are the future of the oil industry." It was the first major event in the history of the WPC in which young professionals and academics had the leading role, and had the opportunity to exchange their ideas in insights on the oil and gas industry with industry leaders and main representatives of the oil and gas industry. Since then, issues of professional development and the disclosure of the creative potential of young industry professionals have been on the agenda of the World Petroleum Council as one of the key areas for the development of international cooperation focused on a strategic perspective. The Future Leaders Forum of the World Petroleum Council VI is the largest international platform for professional communication of young specialists in the oil and gas industry. The contributions in this book are much of interest to professionals and scientists interested or involved in the oil and gas industry or related areas.
OCLC-licensed vendor bibliographic record.
Keywords: World Petroleum Council; Petroleum industry and trade; Gas industry; BUSINESS & ECONOMICS / Industries / General; TECHNOLOGY / Engineering / Civil